Situation of women and pregnant women in Peru. Perspectives from the Peruvian Society of Obstetrics and Gynecology - Ciudad Reynaud, Antonio (2021)
The maternal mortality ratio (MM) in Peru for the year 2020 has been estimated at 81.6 per 100,000 live births, negatively moving away from the downward curve of maternal deaths which from 114.2 per 100,000 live births in 2004 had declined to 55.1 per 100,000 live births in 2019(1). Peru has the same number of maternal deaths to date as in 2012(2). There has been a considerable delay in the goal of reducing maternal mortality, in order to comply with the Millennium Development Goals(3). The explanation for this adverse situation is the COVID-19 infection, which has plagued the world since the beginning of 2020.